Expression Suppression and Activity Inhibition of trpm7 Regulate Cytokine Production and Multiple Organ Dysfunction Syndrome During Endotoxemia: A New Target for Sepsis - Cabello-Verrugio, C (Bentham Science Publishers, 2019)
Background: Main pathological features detected during sepsis and endotoxemia include over-secretion of pro-inflammatory cytokines and multiorgan dysfunction syndrome (MODS). Unfortunately, current clinical efforts to treat sepsis are unsatisfactory, and mortality remains high. Interestingly, transient receptor potential (TRP) melastatin 7 (TRPM7) ion channel controlling Ca2+ and Mg2+ permeability is involved in cytokine production and inflammatory response. Furthermore, TRPM7 downregulation has been shown to alleviate local symptoms in some models of sepsis, but its effects at a systemic level remain to be explored. Objective: To test whether TRPM7 mediates cytokine production and MODS during endotoxemia. Methods: Endotoxemic and sham-endotoxemic rats were subjected to pharmacological inhibition of TRPM7 using carvacrol, or to expression suppression by adenovirus delivery of shRNA (AdVshTRPM7). Then, cytokine and MODS levels in the blood were measured. Results: Inhibition of TRPM7 with carvacrol and suppression with AdVshTRPM7 were both efficient in inhibiting the over-secretion of pro-inflammatory cytokines TNF-α, IL-1β, IL-6, and IL-12, in endotoxemic rats, without inducing downregulation in blood levels of anti-inflammatory cytokines IL-10 and IL-4. Additionally, the use of carvacrol and AdVshTRPM7 significantly prevented liver and pancreas dysfunction, altered metabolic function, and hypoglycemia, induced by endotoxemia. Furthermore, muscle mass wasting and cardiac muscle damage were also significantly reduced by the use of carvacrol and AdVshTRPM7 in endotoxemic rats. Conclusion: Our results indicate TRPM7 ion channel as a key protein regulating inflammatory responses and MODS during sepsis. Moreover, TRPM7 appears as a novel molecular target for the management of sepsis. © 2019 Bentham Science Publishers.